2016
DOI: 10.3390/ijms17071017
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope-Assisted Evaluation of Different Extraction Solvents for Untargeted Metabolomics of Plants

Abstract: The evaluation of extraction protocols for untargeted metabolomics approaches is still difficult. We have applied a novel stable isotope-assisted workflow for untargeted LC-HRMS-based plant metabolomics , which allows for the first time every detected feature to be considered for method evaluation. The efficiency and complementarity of commonly used extraction solvents, namely 1 + 3 (v/v) mixtures of water and selected organic solvents (methanol, acetonitrile or methanol/acetonitrile 1 + 1 (v/v)), with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 40 publications
(51 reference statements)
3
59
0
Order By: Relevance
“…As a cleaner and safer solvent, methyl tert-butyl ether (MTBE) has also been used as an alternative to chloroform for liquid-liquid extraction [50], particularly for the recovery of metabolites and lipids from bacterial, plant, algal, flies, and diverse mammalian samples [41,42,[51][52][53][54][55][56][57][58][59][60]. The use of isotope-labeled internal standards during sample preparation is recommended to assess matrix effects [39,61]. For the selection of suitable solvent(s) and an extraction method that is suitable for different metabolite classes, readers are referred to the available extraction protocol reviews [32,35,39,40,62,63].…”
Section: Sample Extractionmentioning
confidence: 99%
“…As a cleaner and safer solvent, methyl tert-butyl ether (MTBE) has also been used as an alternative to chloroform for liquid-liquid extraction [50], particularly for the recovery of metabolites and lipids from bacterial, plant, algal, flies, and diverse mammalian samples [41,42,[51][52][53][54][55][56][57][58][59][60]. The use of isotope-labeled internal standards during sample preparation is recommended to assess matrix effects [39,61]. For the selection of suitable solvent(s) and an extraction method that is suitable for different metabolite classes, readers are referred to the available extraction protocol reviews [32,35,39,40,62,63].…”
Section: Sample Extractionmentioning
confidence: 99%
“…One is used for the determination of the The wheat ears were milled to a fine powder with a ball mill (MM400, Retsch, Haan, Germany) while being kept in frozen condition. The extraction was performed similarly as reported in (8…”
Section: Sample Preparationmentioning
confidence: 99%
“…application are nutrition (1), evaluation of biosynthetic pathways (2), metabolic engineering (3), flux analysis (2,4), accurate quantification of plant metabolites (5), studies on plant-microbe interactions (6) and untargeted metabolomics and proteomics (6)(7)(8)(9)(10)(11)(12). The increasing popularity of isotopically labelled plant material goes hand in hand with the development of complementary analytical tools e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of plants and plant-derived metabolites labelled with heavy stable isotopes offers an interesting perspective in phytochemical research. Some research fields where stable isotopes found application are nutrition (1), evaluation of biosynthetic pathways (2), metabolic engineering (3), flux analysis (2,4), accurate quantification of plant metabolites (5), studies on plant-microbe interactions (6) and untargeted metabolomics and proteomics (6)(7)(8)(9)(10)(11)(12). The increasing popularity of isotopically labelled plant material goes hand in hand with the development of complementary analytical tools e.g.…”
Section: Introductionmentioning
confidence: 99%